Inter-Regional Collaboration in Gerbangkertosusila for Sustainable Economic Development - Salzabila Indar Parawansa; Choirun Nisa Nur Azijah; Salwa Amalia Firdausi (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2026)
This study was motivated by the persistently high development disparities among regions in Indonesia, particularly in the Gerbangkertosusila region, which have led to unequal economic growth and poor job quality. This study aims to analyze the implementation of inter-regional cooperation and formulate a collaborative model capable of supporting the achievement of Sustainable Development Goal (SDG) 8: decent work and economic growth for all. The method used is qualitative descriptive with a literature review approach, analyzed using the Miles and Huberman interactive model. The results show that inter-regional cooperation has been carried out through Memorandums of Understanding (MoU) and sectoral cooperation, particularly in the fields of transportation and industry, which have improved connectivity and employment opportunities. However, its implementation still faces challenges such as weak coordination, investment disparities, and uneven job quality. This study concludes that a collaborative governance approach serves as an effective solution through institutional strengthening, cross-regional planning integration, and synergy among actors. This model is expected to drive more inclusive economic development and reduce disparities among regions.